Advanced materials, structures and mechanical engineering proceeding of the International Conference on Advanced Materials, Structures and Mechanical Engineering, Incheon, South Korea, 29-31 May 2015 - Kaloop, Mosbeh (CRC Press, Taylor & Francis Group, 2016)
The International Conference on Advanced Materials, Structures and Mechanical Engineering 2015 (ICAMSME 2015) was held on May 29-31, Incheon, South-Korea. The conference was attended by scientists, scholars, engineers and students from universities, research institutes and industries all around the world to present ongoing research activities. This proceedings volume assembles papers from various professionals engaged in the fields of materials, structures and mechanical engineering.